2023
DOI: 10.1371/journal.pone.0279880
|View full text |Cite
|
Sign up to set email alerts
|

Usability and acceptance of a mobile health wallet for pregnancy-related healthcare: A mixed methods study on stakeholders’ perceptions in central Madagascar

Abstract: Background Several sub-Saharan African countries use digital financial services to improve health financing, especially for maternal and child health. In cooperation with the Malagasy Ministry of Health, the NGO Doctors for Madagascar is implementing a mobile health wallet for maternal health care in public-sector health facilities in Madagascar. Our aim was to explore the enabling and limiting factors related to the usability and acceptance of the Mobile Maternal Health Wallet (MMHW) intervention during its i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…This suggested that factors such as cultural norms, values, and economic conditions can affect how individuals engage with smartphone mobile apps for healthcare purposes. Effective community sensitisation emerged as an essential factor for promoting DHI engagement [90]. This involves raising awareness and educating the community about the bene ts and usage of these interventions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that factors such as cultural norms, values, and economic conditions can affect how individuals engage with smartphone mobile apps for healthcare purposes. Effective community sensitisation emerged as an essential factor for promoting DHI engagement [90]. This involves raising awareness and educating the community about the bene ts and usage of these interventions.…”
Section: Discussionmentioning
confidence: 99%
“…Only ve studies explored the challenges and barriers of DHI [90,33,39,41,43]. Of these, three were conducted in Africa [32,90,39], and one in Belgium [41] and the US [43].…”
Section: Challenges and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…However, previous studies on the user profiles of active MMHW users, highlighted that users come from all socio-demographic strata. [18]…”
Section: Limitationsmentioning
confidence: 99%
“…[13] Health Wallet (MMHW) was subsequently developed and implemented in the capital revealing a strong perceived value of mobile money for maternal health, particularly among women from lowerincome backgrounds. [18] Our study aimed to demonstrate a causal effect of COVID-19 lockdowns on the use of digital health services and explore age-dependent differential effects. In the context of maternal health in Madagascar, we examined three primary uses of the MMHW: savings, payments, and voucher use for maternal care.…”
Section: Introductionmentioning
confidence: 99%